Selective catalytic reduction of NOx with NH3 over TiO2 supported metal sulfate catalysts prepared via a sol–gel protocol. (31st July 2020) - Yu, Yanke; Zhang, Jiali; Chen, Changwei; Ma, Mudi; He, Chi; Miao, Jifa; Li, Huirong; Chen, Jinsheng
Abstract : Metal sulfate catalysts exhibited high SO2 tolerance in the NH3 -SCR reaction. The NH3 -SCR reaction mechanism on metal sulfate catalysts should follow the Eley–Rideal mechanism. Abstract : Due to the presence of SO2 in flue gas, SCR catalysts with high SO2 tolerance are desperately required. However, except vanadium-based catalysts, most metal oxide catalysts exhibit low SO2 tolerance. In this research study, CuSO4 /TiO2, Fe2 (SO4 )3 /TiO2, MnSO4 /TiO2, Ce(SO4 )2 /TiO2 and CoSO4 /TiO2 catalysts were prepared via a sol–gel protocol and used in the NH3 -SCR reaction. Low-temperature N2 -sorption, XRD, FT-IR, XPS, H2 -TPR, NH3 -TPD and in situ DRIFTS were used to characterize the physicochemical properties of the prepared catalysts. The presence of SO2 had little influence on the activity of all metal sulfate catalyst samples. CuSO4 /TiO2 showed the highest SCR activity and apparent activation energy among the metal sulfate catalysts following the sequence of CuSO4 /TiO2 < Fe2 (SO4 )3 /TiO2 < MnSO4 /TiO2 < Ce(SO4 )2 /TiO2 < CoSO4 /TiO2 . Characterization results indicated that the amount of acid sites was the main factor that influenced the catalytic activity of the metal sulfate catalysts. The NH3 -SCR reaction of all metal sulfate catalysts followed the Eley–Rideal mechanism: NH3 was first adsorbed at the surface acid sites (Lewis and Brønsted acid sites), and then it reacted with gaseous NO and O2 to form N2 and H2 O. The metal sulfate catalysts, especially CuSO4 /TiO2, should be a promising candidate for vanadium-based SCR catalysts for NO reduction.